Liraglutide Increases VEGF Expression via CNPY2-PERK Pathway Induced by Hypoxia/Reoxygenation Injury - Liu, Chong; Liu, Yong; He, Jing; Mu, Rong; Di, Yanbo; Shen, Na; Liu, Xuan; Gao, Xiao; Wang, Jinhui; Chen, Tie; Fang, Tao; Li, Huanming; et al. (Frontiers in Pharmacology, 2019)
Liraglutide (Lir) is a glucagon-like peptide-1 receptor agonist that lowers blood sugar and reduces myocardial infarct size by improving endothelial cell function. However, its mechanism has not yet been clarified. Unfolded protein response (UPR) plays an important role in the pathogenesis of myocardial ischemia-reperfusion injury (MIRI). It determines the survival of cells. Endoplasmic reticulum position protein homologue 2 (CNPY2) is a novel initiator of UPR that also participates in angiogenesis. To this extend, the current study further explores whether Lir regulates angiogenesis through CNPY2. In our article, a hypoxia/reoxygenation (H/R) injury model of human umbilical vein endothelial cells (HUVECs) was established, Lir effect on HUVECs was first evaluated by CCK-8. Endothelial tube formation was used to analyze the ability of Lir to induce angiogenesis. Subsequently, the effect of Lir on the concentrations of HIF1α, VEGF and CNPY2 were detected by ELISA. To assess whether Lir regulates angiogenesis through the CNPY2-initiated UPR pathway, expression of UPR-related pathway proteins (CNPY2, GRP78, PERK, ATF4) and angiogenic proteins (HIF1α, VEGF) were detected by RT-PCR and Western blot. The results confirmed that Lir significantly increased the expression of HIF1α and VEGF, as well as the expression of CNPY2-PERK pathway proteins in HUVECs after H/R injury. To further validate the experimental results, we introduced the PERK inhibitor, GSK2606414. GSK2606414 was able to significantly decrease both mRNA and protein expression of ATF4, HIF1α and VEGF in vascular endothelial cells after H/R injury. The effect of Lir was also inhibited using GSK2606414. Therefore, our study suggests that CNPY2-PERK pathway is involved in the mechanism of VEGF expression after H/R injury in HUVECs. Lir increases the expression of VEGF through the CNPY2-PERK pathway, which may promote endothelial cell angiogenesis and protect HUVEC from H/R damage.